2015
DOI: 10.1245/s10434-015-4559-3
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia is a Predictor of Postoperative Respiratory Complications in Patients with Esophageal Cancer

Abstract: Sarcopenia may be a predictor of pulmonary complications after esophagectomy. Further analysis is needed to clarify whether nutritional intervention improves skeletal muscle mass and thus contributes to reducing postoperative respiratory complications in sarcopenic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
118
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 170 publications
(129 citation statements)
references
References 30 publications
7
118
3
1
Order By: Relevance
“…The high incidence of pneumonia in sarcopenic patients may be caused by delayed mobilization, sequential paralytic ileus, dysphagia, or difficulty with clearing the airway after gastrointestinal surgery. Sarcopenia was found to be an independent predictor of postoperative respiratory complications in esophageal cancer patients [37]. In this study, preoperative respiratory function was worse in the sarcopenic group, which might have adverse effects on postoperative respiratory complications.…”
Section: Discussionmentioning
confidence: 55%
“…The high incidence of pneumonia in sarcopenic patients may be caused by delayed mobilization, sequential paralytic ileus, dysphagia, or difficulty with clearing the airway after gastrointestinal surgery. Sarcopenia was found to be an independent predictor of postoperative respiratory complications in esophageal cancer patients [37]. In this study, preoperative respiratory function was worse in the sarcopenic group, which might have adverse effects on postoperative respiratory complications.…”
Section: Discussionmentioning
confidence: 55%
“…However, in patients with esophageal squamous cell carcinoma, a high BMI is a predictor of poor prognosis of postoperative survival. Ida et al 65. reported that sarcopenia might be a predictor of pulmonary complications after esophagectomy.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there is significant evidence showing that sarcopenia is independently associated with poor response to cancer therapy in pancreatic (18), breast (19), colorectal (13,20), and renal-cell (21), and hepatic (22) cancer. Sarcopenia carries a high risk of morbidity (23)(24)(25)(26) and confers poor long-term survival after resection of esophageal cancer (27)(28)(29) chemoradiotherapy and esophageal resection cases (7). To our knowledge, our retrospective study is the first report that shows the impact of sarcopenia on patients with unresectable locally advanced esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%